D’une école de paysage à l’autre : retour d’expérience sur un enseignement de la géographie au service des paysagistes - Hervé Davodeau (Projets de Paysage)
How can academics who are not landscape architects find their place and make their discipline useful in the training of landscape architects? This frequently asked question is posed differently according to the discipline and the school. This article focuses on the specific case of a geographer who was first recruited at the Versailles school of landscape architecture and subsequently at the school of landscape architecture in Angers. It provides an opportunity to grasp the structural effects of these institutional frameworks on a teaching method that seeks to adapt to them by being part of specific training courses and to defend the disciplinary fundamentals common to the courses. These two perspectives make it possible to better understand and untangle a number of “pedagogical conundrums” which are characteristic of the teaching of geography considered as a supporting discipline in the training of landscape architects and urban planners. The article partially reproduces the first (pedagogical) volume of a research publication (Davodeau, 2020), which explains its biographical and reflective dimension.